Pra Implementasi Kebijakan Penyelenggaraan Layanan Perpustakaan Pada Dayah Modern di Kabupaten Nagan Raya - Yusnalia, Syarifah; Siraj; Iskandar (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2025)
This study aims to examine the pre-implementation stage of the library service policy at Modern Dayahs in Nagan Raya Regency, in accordance with the mandate of Qanun Aceh Number 9 of 2022 on Library Administration. The focus of the study includes aspects of policy communication, resources, disposition, and bureaucratic structure based on George C. Edwards III’s policy implementation model. A descriptive qualitative approach was used, with data collected through in-depth interviews, observation, and document analysis. The findings reveal that the pre-implementation phase faces several challenges, such as the lack of understanding among dayah administrators regarding the content of the qanun, limited funding and infrastructure, as well as suboptimal coordination among stakeholders. Nevertheless, there is commitment from some parties to support the development of library services integrated with the dayah education system. Therefore, strategic steps such as enhancing policy dissemination, human resource training, and integrated planning are necessary to ensure effective implementation of the policy.